Endogenous Retroviruses Transcriptional Modulation After Severe Infection, Trauma and Burn - Tabone, Olivier; Mommert, Marine; Jourdan, Camille; Cerrato, Elisabeth; Legrand, Matthieu; Lepape, Alain; Allaouchiche, Bernard; Rimmelé, Thomas; Pachot, Alexandre; Monneret, Guillaume; Venet, Fabienne; Mallet, François; et al. (Frontiers in Immunology, 2019)
Although human endogenous retroviruses (HERVs) expression is a growing subject of interest, no study focused before on specific endogenous retroviruses loci activation in severely injured patients. Yet, HERV reactivation is observed in immunity compromised settings like some cancers and auto-immune diseases. Our objective was to assess the transcriptional modulation of HERVs in burn, trauma and septic shock patients. We analyzed HERV transcriptome with microarray data from whole blood samples of a burn cohort (n=30), a trauma cohort (n=105) and 2 septic shock cohorts (n=28, n=51), and healthy volunteers (HV, n=60). We described expression of the 337 probesets targeting HERV from U133 plus 2.0 microarray in each dataset and then we compared HERVs transcriptional modulation of patients compared to healthy volunteers. Although all 4 cohorts contained critically ill patients, the majority of the 337 HERVs was not expressed (around 74% in mean). Each cohort had differentially expressed probesets in patients compared to HV (from 19 to 46). Strikingly, 5 HERVs were in common in all types of severely injured patients, with 4 being up-modulated in patients. We highlighted co-expressed profiles between HERV and nearby CD55 and CD300LF genes as well as autonomous HERV expression. We suggest an inflammatory-specific HERV transcriptional response, and importantly, we introduce that the HERVs close to immunity-related genes might have a role on its expression.